1990
DOI: 10.1073/pnas.87.3.983
|View full text |Cite
|
Sign up to set email alerts
|

Detection of antibody against antigen expressed by molecularly cloned hepatitis C virus cDNA: application to diagnosis and blood screening for posttransfusion hepatitis.

Abstract: A cDNA clone has been derived from the plasma of a chimpanzee with chronic non-A, non-B viral hepatitis (NANBH). We have assayed for antibodies reacting with the encoded antigen in sera from posttrnnsfusion hepatitis patients (643 samples from 23 patients) and their corresponding donors collected during the past 10 years in Japan. The antibody was detected in 15 out of 17 (88.2%) posttransfusion NANBH (PT-NANBH) patients whose sera over time displayed multiple alanine aminotransferase (ALT) peaks. In general, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
1
2

Year Published

1991
1991
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(84 citation statements)
references
References 13 publications
(10 reference statements)
3
78
1
2
Order By: Relevance
“…Patients were from St. Marianna Hospital, Kawasaki, Kanagawa; Tokyo National Chest Hospital, Kiyose, Tokyo; and Shinshu University School of Medicine, Nagano. 12,13 Informed consent was obtained from all patients, and the study had the approval of the Ethical Committees of the hospitals. To study the natural history of acute non-A non-B hepatitis, serial sera samples had been collected over many years and maintained at Ϫ20°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients were from St. Marianna Hospital, Kawasaki, Kanagawa; Tokyo National Chest Hospital, Kiyose, Tokyo; and Shinshu University School of Medicine, Nagano. 12,13 Informed consent was obtained from all patients, and the study had the approval of the Ethical Committees of the hospitals. To study the natural history of acute non-A non-B hepatitis, serial sera samples had been collected over many years and maintained at Ϫ20°C.…”
Section: Methodsmentioning
confidence: 99%
“…11 This assay is used as a surrogate test to estimate the level of HCV-neutralizing (NOB) antibodies. Here we report on the serum antibody responses to HCV structural proteins in a rare group of patients who spontaneously resolved chronic hepatitis C. 12,13 We have found that the appearance and maintenance of high serum titers of NOB antibodies in the course of chronic hepatitis C is accompanied by virus clearance and clinical resolution of liver disease.…”
mentioning
confidence: 99%
“…The cloning of the genome of this causal agent was recently accomplished and the virus was named as hepatitis C virus (HCV) (3). The subsequently established assay, detecting antibodies against core and nonstructural protein of HCV, has revealed that HCV is the major cause of posttransfusion-as well as sporadic community-acquired non-A, non-B hepatitis (4,5). A close relationship between HCV infection and the development of hepatocellular carcinoma (HCC) has also been suggested (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…In the meantime, the epidemiological status of hepatitis C virus (HCV) infection is similar to other areas of the world, with 0.8% prevalence among adult volunteer donors and high prevalences among intravenous drug users, hemodialysis patients, cases positive for antibodies to human immunodeficiency virus, patients with chronic liver disease, and female prostitutes, determined with anti-C100 (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). However, all these data were obtained with the descendants of those having immigrated from the mainland China and been living in the developed plain region of western Taiwan since several hundred yeas ago, and no data concerning the aboriginal ethnic tribes residing in the underdeveloped mountain regions of this island have been obtained.…”
Section: Introductionmentioning
confidence: 96%